Paraquat induces behavioral changes and cortical and striatal mitocondrial dysfunction. - Czerniczyniec, Analia (2011)
Paraquat is a highly toxic quaternary nitrogen herbicide capable of increasing superoxide anion production. The aim of this research was to evaluate various behavioral changes and study cortical, hippocampal, and striatal mitochondrial function in an experimental model of paraquat toxicity in rats. Paraquat (10 mg/kg ip) was administered weekly for a month. Anxiety-like behavior was evidenced in the paraquat-treated group as shown by a diminished time spent in, and fewer entries into, the open arms of an elevated-plus maze. Also, paraquat treatment induced a deficit in the sense of smell. In biochemical assays, NADH-cytochrome c reductase activity was significantly inhibited by 25 and 34% in cortical and striatal submitochondrial membranes, respectively. Striatal cytochrome oxidase activity was decreased by 24% after paraquat treatment. Also, cortical and striatal mitochondria showed 55 and 74% increased State 4 respiratory rates, respectively. Paraquat treatment decreased striatal State 3 oxygen consumption by 33%. Respiratory controls were markedly decreased in cortical and striatal mitochondria, indicating mitochondrial dysfunction after paraquat treatment, together with mitochondrial depolarization and increased hydrogen peroxide production rates. We demonstrate that paraquat induced alterations in nonmotor symptoms and cortical and striatal mitochondrial dysfunction.